Prevention and Mitigation of Oil Waste In Coastal Areas For Fishing Communities - Pauhesti Pauhesti; Ade Kurniawan Saputra; Harin Widiyatni; Sri Feni Maulindani; Riskaviana Kurniawati; Albert Kalasnikova Suparmanto; Lailatul Wastiyah; Muhammad Raihan Azica; Theresia Dolfina Kilmas (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
Oil spills in coastal areas are a serious environmental issue that can cause damage to marine ecosystems, water pollution, and economic losses for fishing communities. This community service project aims to enhance fishermen's understanding of the negative impacts of oil spills and to provide practical skills and knowledge regarding oil waste management. The approach used includes training on the use of absorbent tools, binding chemicals, and localization technologies to handle oil spills. Additionally, the project introduces environmentally friendly technologies to reduce the risk of oil leaks or spills from fishing vessels. The project results indicate a significant increase in the knowledge and skills of the participating fishermen regarding oil waste management. Further discussion reveals the importance of implementing comprehensive coastal area management strategies to prevent and mitigate oil pollution. In conclusion, this project not only successfully achieved its goal of enhancing fishermen's capacity but also offers a replicable model for similar programs in other coastal areas. Therefore, active participation from fishing communities and continuous support from various stakeholders is essential for environmental sustainability and the well-being of coastal communities.